STUDI TENTANG SULAMAN BAYANG BENTUK, TEKNIK DAN PENEMPATAN MOTIF PADA BAJU, MUKENA DAN JILBAB DI KENAGARIAN PANAMPUANG KECAMATAN AMPEK ANGKEK - RESI MANDA SARI, Dra. Ernis, M.Pd, Dra. Jupriani, M.Sn (Serupa The Journal of Art Education, 2014)
The porpoes of this research are: 1) to desribe of the sulaman bayang’s design in Panampuang Village Ampek Angkek District, 2) to desribe of the sulaman bayang’s technics in Panampuang Village Ampek Angkek District, 3) to desribe of the placement of sulaman bayang’s in Panampuang Village Ampek Angkek District.This is qualititatif research which is use descriptive approach in Panampuang Village Ampek Angkek District. The data resources taken the craftsman and the entrepreneurs in sulaman bayang’s in Panampuang Village. The data resources is collecting from observation, interview and documentation, such as photographs and references related to the variable of the reseources. The technics of this data analisis this descriptive approach are: 1) the data reduction, 2) arrenging/presenting the data, 3) the verification/conclusion.The result of this study found some names of sulaman bayang’s design in Village Panampuang, they are bungo mawar, bungo melati, bungo kacumbuang, ros pacah, kupu-kupu, relung, bungo M and trompet design. The design of sulaman bayang’s taken from plants and animal in Panampuang Village use tikam jejak for line shaped design such as stem and sticks flannel for design as the shape of leaves and flower. The plecement of design in Panampuang Village they were placed on the edge/edge products, middle and blushes.Keywords : design, technic, placement of sulaman bayang’s